(Invited) Novel Integrated Circuit Platforms Employing Monolithic Silicon CMOS + GaN Devices. (23rd August 2016) - Fitzgerald, Eugene A; Lee, K.E.; Zhang, Li; Huang, C.C.; Kadir, A.; Bao, Shuyu; Ren, Z.; Wang, C.; Wang, Y.; Lee, Kwang Hong; Liu, Z.H.; Palacios, Tomas; et al.
Abstract : We describe the research results produced from our focus on integrating GaN HEMTs and LEDs into silicon CMOS integrated circuits. Although current component markets are driving most GaN HEMT development, we have undertaken an innovation path in which the value of an integrated GaN device in a silicon design environment is the driver for materials and device development. Our integrated process flow employs standard foundry production of front and back end CMOS. Such constraints demand certain GaN epitaxial and material criterion that is different than those on non-integrated devices. We report on 200 mm GaN-on-Si 725 um thick engineered substrates formed through a combination of MOCVD and wafer bonding processes. We have developed wafer engineering techniques such as edge encapsulation and substrate replacement to address wafer fragility issues typically associated with GaN on SEMI-spec 725 um Si wafers. This also leads new wafer/device platforms such as GaN-OI and CMOS + GaN that will open new avenues in device performance and integration of III-N with Si CMOS.